ANALISIS PENGARUH OVERSAMPLING SMOTE CREDIT CARD FRAUD DETECTION METODE FITUR FORWARD SELECTION - Wijaya, Louise Ernest; Fancella, Shevira; Sihombing, Oloan (Politeknik Bisnis Indonesia, 2025)
Credit card is one of the legal payment methods that is still widely used by the society. People use credit cards to buy various needs both in terms of food, clothing and food. Credit cards also present many dis-count and vouchers that can attract more and more users every day. But in the increasingly crowded use of credit cards, there are also cyber threats that are also growing rapidly along with the times. One of them is fraud to obtain data containing credit card information of an individual. To prevent/lower the risk of Cyber Crime, a credit card fraud detection method is needed. This research focuses on the influence of SMOTE oversampling and Forward Selection feature in the performance of a system used.